Agent-based simulation model for evacuation operations in fire disasters - Abusalama, Jawad; Razali, Sazalinsyah; Choo, Yun Huoy; Attajer, Ali (Inderscience Publishers, 2025)
Fire disasters pose significant challenges for timely evacuation due to various factors like human behaviour and structural configurations. This paper aims to address this issue by developing an intelligent agent-based simulation model for evacuation operations during such disasters. The model facilitates critical decision-making for efficient evacuation, where five intelligent agents are utilised in the model to simulate realistic scenarios. Evaluation through comparison studies and sensitivity analysis demonstrates the efficacy of the developed model. Results indicate its superiority over three alternative models in most experiments. Effective evacuation operations are crucial in minimising the severe consequences of fire disasters and saving lives. This paper contributes to the advancement of methods for managing such crises, ultimately reducing losses and enhancing disaster preparedness.